Strategic environment and bank performance; (Empirical study of bank listed in Indonesian stock exchange period 2011-2015) - Mursalim Nohong (Journal of Economics, Business, and Accountancy Ventura, 2016)
This study aimed to explain the interaction between macroeconomic and the internal environment with the performance of banks in Indonesia. The analysed data obtained from 10 banks for 5-year observation period by using descriptive and inferential analysis through PLS program. The results showed that the BI rate is the most significant indicator in measuring changes in the macro environment, the efficiency ratio indicators for internal environment variables and indicators ROA for the variable performance. Further analysis showed that changes in the macro environment do not significantly influence the efficiency and performance of the banking system. However, efficiency is measured by using a ratio BOPO significant effect on performance.